NPS MedicineWise application in supporting medication adherence in chronic heart failure: an acceptability and feasibility pilot study - Chapman-Goetz, Jessica; Packham, Nerida; Yu, Kitty; Gabb, Genevieve; Potts, Cassandra; Prosser, Adaire; Arstall, Margaret A.; Burdeniuk, Christine; Chan, Alicia; Wilson, Teena; Hotham, Elizabeth; Suppiah, Vijayaprakash (Frontiers in Digital Health, 2023)
Introduction Heart failure (HF) is an increasing global concern. Despite evidence-based pharmacotherapy, associated morbidity and mortality remain high. This study aimed to assess the acceptability, feasibility, and value of the NPS MedicineWise dose reminder app in a tiered, pharmacist-led intervention to address medication non-adherence in patients with HF. Methods This prospective, single-blinded, randomised controlled trial recruited 55 patients with HF between September 2019 and October 2020. Participants were randomly assigned to either the intervention or control arms. Intervention participants used the app which prompted medication administration at each dosing interval. Control participants received standard care and remained blinded to the app throughout the study. Treatment non-adherence prompted a tiered, pharmacist-led intervention. Comparison of the Self-Efficacy for Appropriate Medication Use Scale (SEAMS) at baseline and 6-months measured the app's value in supporting medication adherence. Secondary outcome measures included self-reported medication knowledge, health-related quality of life, psychological wellbeing, and signs and symptoms of HF. Data were analysed using standard statistical tests with significance set at α 0.05. Results Approximately half of respondents reported managing HF and medications better by using the MedicineWise app (Tier 1). Most respondents expressed satisfaction with the in-app messages (Tier 2) and pharmacists' phone calls (Tier 3). The intervention participants demonstrated a significant improvement in the SEAMS between baseline and 6-months follow-up. Discussion It is feasible and potentially of value to use the MedicineWise app with a tiered, pharmacist-led intervention to support medication adherence in patients with HF. Our findings provide clinicians with “real-world” information on the practicality and potential value of using mobile health to support treatment adherence in patients with HF. Trial registration number Australian New Zealand Clinical Trials Registry Clinical trial registration number: ACTRN12619000289112p (http://www.ANZCTR.org.au/ACTRN12619000289112p.aspx)